دراسة سلوك الجوائز البيتونية المقواة خارجياً بصفائح من الـGFRP تجريبياً - غاندي علي جحجاح; قصـي علي نداف; ميرفت حسن حشمة (Tishreen University, 2019)
يهدف هذا البحث إلى دراسة السلوك الإنشائي للجوائز البيتونية المسلحة غير المتشققة والمقواة خارجياً بصفائح من الألياف الزجاجية GFRP, وذلك من خلال برنامج تجريبي يتضمن مجموعتين من الجوائز البيتونية بسيطة الاستناد,  الأولى  معيارية B1 مكونة من جائزين, والثانية B2 تضم جائزين مقويين بصفائح من الـGFRP  ملصوقة على الوجه المشدود. تتكون الصفائح من ألياف زجاجية من النوع E محضرة باستخدام لاصق لاعضوي (polyster ), وهي ذات مقاومة عالية على الشد. اختبرت الجوائز تحت تأثير قوتين مركزتين في ثلث المجاز وصولاً إلى مرحلة الانهيار, حيث تشير النتائج التجريبية إلى فعالية هذه التقوية في رفع الجودة الإنشائية للجوائز المقواة وذلك بزيادة قدرة التحمل, وتخفيض السهم المقابل للحمولة القصوى, بالإضافة إلى تأثيرها على آلية انتشار التشققات  ودورها في زيادة قوة القص اللازمة لتشكل الشق القطري الرئيسي المسبب للانهيار وتأخير تشكله. The overall objective of this paper is to establish the structural behavior of uncracked reinforced concrete beams strengthened with externally bonded glass-fiber reinforced plastic (GFRP) sheets. This is done through an experimental program that includes two groups of simple supported concrete beams: B1 is specimen unplated and B2 is with bonded GFRP plates on the tension face, which are made from E- glass fibers in an isophathalic polyster inorganic adhesive system and has a high tensile strength. These beams were constructed and load-tested in four-point flexure with loads at one-third point up to failure. Experimental results indicate to the effectiveness of this  technique in improving  the  structural ductility of strengthened beams through increasing the load  capacity, and its contribution in reducing the midspan deflection versus the ultimate load, in addition to  its effect on cracks distribution and its role in improving the shear force required to form the major diagonal crack, which causes failure, thus  delaying  its appearance.